2018
DOI: 10.1371/journal.pone.0191306
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of cell-based therapy combined with descemetorhexis for treating Fuchs endothelial corneal dystrophy in rabbit model

Abstract: Corneal transparency is maintained by the corneal endothelium through its pump and barrier function. Severe corneal endothelial damage results in dysregulation of water flow and eventually causes corneal haziness and deterioration of visual function. In 2013, we initiated clinical research of cell-based therapy for treating corneal decompensation. In that study, we removed an 8-mm diameter section of damaged corneal endothelium without removing Descemet’s membrane (the basement membrane of the corneal endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 33 publications
0
32
1
4
Order By: Relevance
“…Although Descemet's stripping automated endothelial keratoplasty (DSAEK) and Descemet membrane endothelial keratoplasties (DMEK) are now the most commonly used surgical method of endothelial keratoplasty [25][26][27], the anterior chamber injection method may be a very promising method to be clinically used. Recently, Okumura reported serial studies showing that injection of cultivated corneal endothelial cells with Rock inhibitor (Y-27632) into rabbit or monkey anterior chambers could exert good therapeutic effect for corneal endothelial dysfunction [28][29][30][31]. The Y-27632 could signi cantly promote cell adhesion and proliferation, and inhibit apoptosis of corneal endothelial cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although Descemet's stripping automated endothelial keratoplasty (DSAEK) and Descemet membrane endothelial keratoplasties (DMEK) are now the most commonly used surgical method of endothelial keratoplasty [25][26][27], the anterior chamber injection method may be a very promising method to be clinically used. Recently, Okumura reported serial studies showing that injection of cultivated corneal endothelial cells with Rock inhibitor (Y-27632) into rabbit or monkey anterior chambers could exert good therapeutic effect for corneal endothelial dysfunction [28][29][30][31]. The Y-27632 could signi cantly promote cell adhesion and proliferation, and inhibit apoptosis of corneal endothelial cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…Potential future alternatives to EK that could help address the not fulfilled demand for donor corneas and reduce the growing waiting list include removing central guttae and regenerating a central endothelial cell layer from healthy peripheral cells in patients with Fuchs' dystrophy [ 37 ] or injecting cultured human corneal endothelial cells into the anterior chamber to rehabilitate corneas without residual healthy endothelium and recover of the corneal transparency [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…An analogous situation exists with therapeutic HCEnC injection, which will require removal of central endothelium using a scraping technique to make room on the host DM for injected cells. 21 Studies of cell injection in felines have shown that scraping a larger segment of host endothelium is correlated with significantly worse outcomes, while eyes with smaller scraped areas demonstrated recovery even without injection of cells. 37 Similar to DMET/DWEK/DMT, eyes with a larger EAL may possess more HCEnCs capable of stimulating regeneration at the edges of the scraped endothelial wound; therefore, host EAL may influence the optimal amount of endothelium to be removed.…”
Section: Discussionmentioning
confidence: 99%
“… 18 20 A portion of the host endothelium must be cleared before injection to facilitate attachment of injected cells to the native DM, and determination of the amount of endothelium to be removed will require knowledge of the endothelium/DM size. 12 , 21 As such, it would be beneficial to identify an accurate in vivo measurement parameter of the host endothelium/DM complex. Furthermore, to this point the TZ has been characterized only in vitro, via scanning electron microscopy (SEM) 22 or immunostaining.…”
Section: Introductionmentioning
confidence: 99%